Non-fluoroscopic vs. fluoroscopic radiofrequency catheter ablation for pediatric atrioventricular nodal reentrant tachycardia: a comparative study of procedural characteristics and ablation site - Chuang, Chieh-Mao; Lee, Pi-Chang; Tai, I-Hsin; Peng, Ying-Hsuan; Fan, Wen-Po; Lee, Yu-Shin; Lin, Ming-Chih; Jan, Sheng-Ling; Fu, Yun-Ching; Chen, Shih-Ann (Frontiers in Cardiovascular Medicine, 2025)
BackgroundNon-fluoroscopic cryoablation is considered safe for pediatric atrioventricular nodal reentrant tachycardia (AVNRT), but concerns about prolonged procedures and recurrence persist, requiring continued use of radiofrequency ablation (RFA). Non-fluoroscopic RFA, guided by three-dimensional mapping, offers enhanced precision. This study compares its safety and effectiveness with fluoroscopic RFA in pediatric AVNRT.MethodsWe retrospectively analyzed children undergoing RFA without (X− group) or with (X+ group) fluoroscopy at multiple centers (2011–2024). Patients who received fluoroscopic and three-dimensional mapping guidance were excluded. Baseline characteristics, electrophysiological data, and ablation outcomes were compared.ResultsAmong 119 patients (X+, 57; X−, 62), there was a significantly higher rate of successful ablation sites in the lower Koch triangle on 3D electroanatomical mapping (3D-EAM). However, the procedure time, acute success rate, recurrence-free survival of AVNRT, and injury to the conduction system were similar between the groups. No permanent complete atrioventricular block was observed in either group. The longer procedure time was independently correlated with ablation location outside of the low Koch triangle, lower common pathway block, and slow pathway modification. Dual AV nodes without inducible tachycardia had lower AVNRT-free survival than typical and atypical AVNRT (80% vs. 96.5% vs. 100%, p = 0.025). Younger children can achieve successful ablation with fewer ablation pulses and a smaller ablation catheter profile, with similar recurrence and conduction system injury.ConclusionsNon-fluoroscopic RFA, guided by 3D-EAM, achieves comparable acute and mid-term outcomes to fluoroscopic RFA in pediatric AVNRT. The successful site of slow pathway ablation was significantly lower when using 3D-EAM compared with fluoroscopy.